2019
DOI: 10.1097/md.0000000000016449
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of cervical elastography in predicting preterm delivery

Abstract: Background: The aim of the study was to evaluate the diagnostic accuracy of cervical elastography in predicting preterm delivery (PTD). Methods: We searched the PubMed, EMBASE, and Cochrane databases to identify relevant studies that applied ultrasound (US) elastography to assess cervical stiffness and predict PTD. All the studies were published before December 11, 2018, and only studies published in English were collected. The cervical length (CL) was considered a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 38 publications
(72 reference statements)
0
24
2
1
Order By: Relevance
“…A soft cervix (identified by shear-wave elastography) at 18-24 weeks of gestation increases the risk of sPTB <37 and <34 weeks of gestation independently of cervical length. Moreover, in a recent meta-analysis [75] of seven studies that included 1488 pregnant women, cervical elastography showed a sensitivity of 0.84 and a specificity of 0.82. The authors concluded that cervical elastography is a promising and reliable method to predict a PTB.…”
Section: The Role Of Cervical Elastographymentioning
confidence: 99%
“…A soft cervix (identified by shear-wave elastography) at 18-24 weeks of gestation increases the risk of sPTB <37 and <34 weeks of gestation independently of cervical length. Moreover, in a recent meta-analysis [75] of seven studies that included 1488 pregnant women, cervical elastography showed a sensitivity of 0.84 and a specificity of 0.82. The authors concluded that cervical elastography is a promising and reliable method to predict a PTB.…”
Section: The Role Of Cervical Elastographymentioning
confidence: 99%
“…Various works have reported the use of the shear wave group speed V g as a surrogate for cervical softness in primates and humans [20,23,24,30,[55][56][57][58]. For example [59], reported a decrease in the group speed of shear waves between ripened and unripened ex vivo human cervical samples, 39% for the anterior region and 25% for the posterior region with a p value < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Allowing detection of changes in tissue elasticity, elastography is a complementary technique to B-mode imaging, and it includes two methods, namely, shear-wave and strain elastography. A recent meta-analysis showed that the performance of cervical elastography was better than cervical length in the prediction of preterm delivery [ 37 ]. For the prediction of outcome of induction of labor, models based on inner cervical shear wave elastography and cervical length were more accurate than models based on the Bishop score [ 38 ].…”
Section: High-resolution Ultrasonographymentioning
confidence: 99%